Classification, investment selection, and valuation of new venture and startups companies - Securato Junior, Jose Roberto (2021)
This thesis examines how investment selection and valuation of new ventures and startup companies vary along those companies\' life cycle. A three-phased research approach included i) a literature review on new ventures and startups, ii) a 105-investors survey and public interviews on investors\' perspectives, and iii) robust regressions of expected returns along the life cycle of new ventures and startups. There are vital pieces of evidence that investors\' expectations vary along the life cycle of new ventures and startups. Newer ventures are focused on survival, whereas older ventures aim at becoming relevant. The investors\' perception of risk and expected return change significantly as the new venture overcomes obstacles and reaches certain milestones. This thesis presents the Life Cycle Valuation Method, filling a void in the valuation of new ventures and startups.